Smartphone Data Capture Efficiently Augments Dictation for Knee Arthroscopic Surgery. Issue 3 (1st February 2020) - Featherall, Joseph; Oak, Sameer R.; Strnad, Gregory J.; Farrow, Lutul D.; Jones, Morgan H.; Miniaci, Anthony A.; Parker, Richard D.; Rosneck, James T.; Saluan, Paul M.; Spindler, Kurt P.
Abstract : Introduction: The objectives of this study are (1) to develop a provider-friendly, evidence-based data capture system for lower-limb orthopaedic surgeries and (2) to assess the performance of the data capture system on the dimensions of agreement with operative note and implant log, consistency of data, and speed of provider input. Methods: A multidisciplinary team developed a database and user interfaces for Android and iOS operating systems. Branching logic and discrete fields were created to streamline provider data input. One hundred patients were randomly selected from the first four months of data collection (February to June 2015). Patients were limited to those undergoing anterior cruciate ligament reconstruction, meniscal repair, partial meniscectomy, or a combination of these procedures. Duplicate data on these 100 patients were collected through chart review. These two data sets were compared. Cohen's kappa statistic was used to assess agreement. Results: The database and smartphone data capture tool show almost perfect agreement (kappa > 0.81) for all data tested. In addition, data are more comprehensive with near-perfect provider completion (100% for all data tested). Furthermore, provider data entry is extremely efficient (median 151-second completion time). Conclusion: A well-designed database and user-friendly interface have greater potential for research utility, clinical efficiency, and, thus, cost-effectiveness when compared with standard voice-dictated operative notes. Widespread utilization of such tools can accelerate the pace and improve the quality of orthopaedic clinical research. Level of Evidence: Level IV